DEFINITION OF CRITERIA FOR EVALUATION OF LEVELS FORMATION OF PROFESSIONAL AND PEDAGOGICAL CULTURE PRIMARY CLASS TEACHER (Pedagogy of Higher and Secondary Education, 2022)
In the article problems of definition of criteria of an estimation of levels of formation of professional – pedagogical culture of the teacher of initial classes are considered. The analysis of the pedagogical literature problem of professional and pedagogical culture carried out, criteria of professional – pedagogical culture  of students are determined.
Keywords: professional-pedagogical culture; culture; pedagogical culture